(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
A method for the synthesis of complex compounds of metals with 2-(3- Hydroxypropylbenzimidazole acetates, chlorides and nitrates of Co(II), Ni(II) and Cu(II) has been developed method for the synthesis of complex compounds of metals with 2-(3- Hydroxypropylbenzimidazole acetates, chlorides and nitrates of Co(II), Ni(II), Cu(II), as well as analysis of the composition and structure of synthesized complex compounds using modern physicochemical methods using IR spectroscopy and EDH analyses has been developed. It was found that the ligand 2-(3-Hydroxypropyl) benzimidazole is coordinated through a nitrogen atom in the imidazole ring in complexation reactions., as well as analysis of the composition and structure of synthesized complex compounds using modern physico-chemical methods using IR spectroscopy and EDH analyses. It was found that the ligand 2-(3-Hydroxypropyl) benzimidazole is coordinated through a nitrogen atom in the imidazole ring in complexation reactions